Understanding How Individuals Overcome Their Dyslexia: Struggles, Turning Points in Life, and Advice - Kuo, Nai Cheng; Fisher, Karin M.; Jones, Jennifer; Hillis, Sara; Chen, I.-Chien; Stanley, Keonna (Journal of the American Academy of Special Education Professionals, 2022)
Dyslexia is a neurological condition in the brain that causes individuals to experience difficulties in reading. It exists around the world and affects about 20% of the population in the United States. Yet, many still go through their early education, either undiagnosed or not receiving the proper instructional support to be successful. In the present study, we conducted a mixed-method study of 116 stories of people who overcame their struggles with dyslexia by analyzing interview data via Understood.org. We synthesized the data by answering three questions designed to reveal their dyslexia struggles, turning points in life when interviewees used dyslexia to their advantage, and advice from their personal experiences to encourage others with dyslexia. Learning from their stories will inspire students with dyslexia and help educators identify ways to support this group of students. Implications for educational practices and future research are discussed.